Realizing 1, 1‐Dehydration of Secondary Alcohols to Carbenes: Pyrrolidin‐2‐ols as a Source of Cyclic (Alkyl)(Amino)Carbenes. (6th May 2022) - Das, Ayan; Elvers, Benedict J.; Nayak, Mithilesh Kumar; Chrysochos, Nicolas; Anga, Srinivas; Kumar, Amar; Rao, D. Krishna; Narayanan, Tharangattu N.; Schulzke, Carola; Yildiz, Cem B.; Jana, Anukul
Abstract: Herein we report secondary pyrrolidin‐2‐ols as a source of cyclic (alkyl)(amino)carbenes (CAAC) for the synthesis of CAAC‐Cu I ‐complexes and cyclic thiones when reacted with Cu I ‐salts and elemental sulfur, respectively, under reductive elimination of water from the carbon(IV)‐center. This result demonstrates a convenient and facile access to CAAC‐based Cu I ‐salts, which are well known catalysts for different organic transformations. It further establishes secondary alcohols to be a viable source of carbenes—realizing after 185 years Dumas' dream who tried to prepare the parent carbene (CH2 ) by 1, 1‐dehydration of methanol. Addressed is also the reactivity of water towards CAACs, which proceeds through an oxidative addition of the O−H bond to the carbon(II)‐center. This emphasizes the ability of carbon‐compounds to mimic the reactivity of transition‐metal complexes: reversible oxidative addition and reductive elimination of the O−H bond to/from the C(II)/C(IV)‐centre. Abstract : The thermal dehydration of secondary alcohols to carbenes and reverse back‐hydration are showcased. The in situ generation of cyclic (alkyl)(amino)carbenes through the thermal 1, 1‐dehydration of secondary pyrrolidin‐2‐ol alcohols was realized and utilized for various purposes such as the synthesis of transition metal‐carbene complexes. This methodology opens a door for further consideration of various secondary alcohols as sources of carbenes.